Face, Power, and Digital Discourse: A Pragmatic Analysis of Politeness in Asynchronous Student-Lecturer Exchanges - Belay Sitotaw Goshu; Muhammad Ridwan (LingLit Journal Scientific Journal for Linguistics and Literature, 2025)
The rapid digitization of higher education has transformed student-lecturer communication, with asynchronous platforms becoming primary sites of academic interaction. However, the pragmatic dimensions of these exchanges, particularly how face and power are negotiated through politeness strategies, remain underexplored in digital contexts. This study investigates how students and lecturers manage face and negotiate power through politeness strategies in asynchronous digital exchanges, examining strategy selection across participant roles and communicative purposes. Employing a qualitative interpretive paradigm with computer-mediated discourse analysis (Herring, 2004), we analyzed 1,847 asynchronous exchanges from Blackboard Learn at Dire Dawa University, Ethiopia. Participants included 16 lecturers and 275 students across Business, Engineering, and Social Sciences. Data were coded deductively using Brown and Levinson's (1987) politeness framework and inductively for emergent digital-specific patterns. Statistical analysis included chi-square tests and odds ratios. Significant asymmetries characterized strategy selection: students predominantly employed deferential strategies (negative politeness: 36.8%; off-record: 19.1%), while lecturers favored bald on-record strategies (41.2%). Request sequences showed extensive student mitigation (hedging: 82.3%; apologetic framing: 58.7%) versus lecturer directness (bald on-record: 52.8%). Feedback followed a "sandwich structure" (opening positive: 78.5%; closing positive: 72.8%). Time-sensitive contexts reduced mitigation by 58%, temporarily overriding power norms. Resistance patterns revealed student agency through polite pushback (26.3%) and justified disagreement (19.8%), with lecturers responding accommodatively (explanation: 25.1%; compromise: 22.0%). Repair sequences showed role-dependent preferences: student-initiated apology (92.5% success) and lecturer-initiated explanation (87.3% success). Asynchronous digital discourse both reproduces institutional power asymmetries and enables novel forms of negotiation through platform-specific affordances. Effective face-work requires strategy-role alignment, with digital mediation transforming traditional politeness practices. Universities should develop communication guidelines acknowledging power asymmetries, provide faculty training on feedback structures and accommodative responses, and offer student orientation on pragmatic norms. Platform designers should incorporate features supporting face-work in asynchronous academic discourse.